BUSINESS COMMUNICATION ETHICS - Suhairi; Farach Nur Fachri; Mutiara Khinaya; Arjuna Pangestu (International Journal of Economic Research and Financial Accounting, 2023)
Business communication ethics is a set of principles and guidelines that govern behavior in business communication. This study aims to explore the importance of business communication ethics and its impact on relationships with customers, employees and other stakeholders as well as organizational image. The research method used is literature study, by collecting and analyzing literature relevant to the research topic. The results of the study show that the application of business communication ethics can help build good relationships with customers, employees and other stakeholders as well as maintain a positive image for the organization